Diversity, abundance and distribution of fishes in Bulubulu river (Revista Científica Ciencias Naturales y Ambientales, 2021)
A study was done on the Bulubulu river located in the province of Guayas, with the aim of obtaining a record of the diversity, abundance and distribution of the ichthyofauna present in ten stations, using two fishing gear. As a result, 428 individuals were captured, belonging to five orders, nine families, 13 genera, and 14 species. The most abundant species were Astyanax festae and Brycon dentex with 90 individuals each, followed by Brycon alburnus with 84 individuals, the rarest species in the place were Astroblepus sp. And Chaetostoma fischeri with one individual each. The species with greater distribution were A. festae and B. dentex, being in 7 stations each. Regarding diversity, the sampling area obtained a Shannon index of 2.03 (average diversity), and stations with high values were only 1 and 2, with values of 1.73 and 1.6 respectively.
Keywords: Ichthyofauna; Distribution; Diversity; Abundance; Shannon index